STUDI PSIKOLOGI SASTRA TOKOH BIMA - Harpen Dwi Jaksana; Sunardi Sunardi; Ahmad Arif Musadad (Jantra., 2019)
Literary works are a means of connecting messages that manifest in psychological symbols. Bima, who is a character in a literary work of the archipelago, possesses various meanings. Bima is always seen as a knight in the Mahabharata epic. His other side which is rarely seen is from the psychological point of view which is closely related to agrarian culture. Using the textual approach in literary psychology, this study examines the connection between Bima figure andagrarian culture. The explanation then becomes the basis of indoctrination to reflect the past agrarian culture to maintain contemporary agrarian culture.